Analysis of Junior High School Students’ Problem-solving Ability Reviewed from Self-regulated Learning - A S Bayuningsih; B Usodo; S Subanti (Universitas Sebelas Maret, 2017)
Problem-solving ability in mathematics is a primary means to understand a problem and develop the students ' ability in solving a problem. Step in solving problems are categorized to understanding the problem, devising a plan, carrying out the plan and reflection. This research used a descriptive method aimed to identify the problem-solving ability among junior high school students and review from students self-regulated learning (SRL).The subjects of the research were taken by one student in each SRL category (high, medium, and low) which then given the problem-solving test and the result was triangulated by interview. Based on the research, it can be stated that the students with high self-regulation can solve a mathematical problem by applying first indicator, the second indicator, third indicator, but they cannot apply the fourth indicator. The students with medium self-regulation can apply the first indicator and second indicator while they are still having the problem in third indicator and fourth indicator. The students with low category self-regulation cannot apply all of those in solving the mathematical problem.